Quality and Quantity Revisited - Piovani, Juan Ignacio (2015)
This paper attempts to discuss the qualitative methodological approach of Jack Katz in itshistorical framework of production. In doing so, we aim to analyze the actual relevance of thesediscussions and their impact in the qualitative-quantitative dilemma. Revisiting Katz´s ideas andcomplementing them with some critical remarks about the limits, misuses and biases of the four R (representativeness, reactivity, reliability and replicability) in quantitative research implies asignificant contribution to the understanding of qualitative research?s value in its own terms. Inmany ways, Katz?s methodological ideas anticipate later developments.